MiR-499a-5p Promotes the Proliferation and Migration of Uterine Leiomyoma Cells by Activating the Wnt/β-Catenin Signaling Pathway - Ni J; Ma Y; Qiu J (International Journal of Women's Health)
Jingjing Ni, Yan Ma, Jianping Qiu Department of Obstetrics and Gynecology, The Affiliated Suzhou Hospital of Nanjing Medical University (Suzhou Municipal Hospital), Suzhou, Jiangsu, 215000, People’s Republic of ChinaCorrespondence: Jianping Qiu, Email 15722703657@163.comObjective: This study aimed to investigate the functional role and underlying mechanism of miR-499a-5p in the progression of uterine leiomyoma (ULM).Methods: Expression levels of miR-499a-5p were analyzed in ULM tissues and cells. Functional assays were conducted to evaluate the effects of miR-499a-5p knockdown or overexpression on cellular proliferation, migration, apoptosis, and cell cycle progression. The involvement of the Wnt/β-catenin signaling pathway was assessed using pathway-specific protein markers and lithium chloride (LiCl) as a chemical activator.Results: miR-499a-5p was significantly upregulated in ULM tissues and cells. Its knockdown inhibited proliferation and migration, induced apoptosis, and caused cell cycle arrest at the G0/G1 phase. Additionally, downregulation of miR-499a-5p suppressed the activation of the Wnt/β-catenin pathway, an effect that was reversed by LiCl treatment.Conclusion: miR-499a-5p facilitates the development of uterine leiomyoma by activating the Wnt/β-catenin signaling pathway. These findings suggest that miR-499a-5p may serve as a promising molecular biomarker and a potential therapeutic target for ULM management.Keywords: miR-499a-5p, uterine leiomyoma, Wnt/β-catenin signaling pathway, proliferation, migration